Teaching Mathematics History as a Teaching Resource from High School Education Curricular Guidelines in Costa Rica (1949 – 2012) - Castro-Soto, Leonel (2016)
In Costa Rica, the 2012 curricular reform introduced the history of mathematics as a discipline central concept, awarding it a leading role in the teaching-learning process. This article describes the evolution that study programs have had as a thread for teaching mathematics in high school education in Costa Rica between 1949 and 2012. In particular, it highlights the curricular approaches on the use of the history of mathematics as a teaching resource. In the study programs analyzed, the study has allowed to recognize two specific trends of this use: History is a motivating element for students, and history is a didactic planning methodological tool for teaching staff.